The feasibility of Picture-Based insurance (PBI): Smartphone pictures for affordable crop insurance - Ceballos, Francisco; Kramer, Berber; Robles, Miguel (International Food Policy Research Institute, 2019)
Smallholder farmers are increasingly exposed to weather extremes but lack access to affordable insurance products to protect their livelihoods from catastrophic crop damage. This paper analyzes the feasibility of Picture-Based Insurance (PBI) as a tool to improve the quality and affordability of crop insurance. Under PBI, insurance claims are verified using a time-lapse of pictures from insured plots, both pre- and post-damage, taken by farmers themselves using regular smartphone cameras. PBI aims at minimizing asymmetric information and costs of claims verification compared to indemnity insurance, while reducing basis risk and improving trust, tangibility, and understanding compared to index-based insurance. A pilot implementation in the rice-wheat belt of India speaks to PBI being a feasible and valuable complement to existing insurance products. Damage is visible from smartphone pictures, farmers can take pictures of sufficient quality for loss assessment, and PBI helps reduce severe downside basis risk at minimal cost.